Position und Entwicklungsdynamik des Deutschen als Fremdsprache international – im Blick der angewandten Linguistik. Position and development dynamics of German as a Foreign language international – in the view of Applied Linguistics. - Földes, Csaba (Glottodidactica, 2016)
This paper is concerned with a statistically firm inventory of the international status of German as a Foreign Language. While presenting numbers of learners throughout the world it also focusses geographically and in content on the cultural area of Central and Eastern Europe, in particular the so called Visegrád Group. The aim is therefore to investigate trends and tendencies in the development of German as a Foreign Language. On a meta-level it deals with language policy for German by pleading for a reinforced integration of language promotion policies in Applied Linguistics.